Aspirin and NSAIDs for breast cancer chemoprevention. Issue 5 (September 2015) - Yiannakopoulou, Eugenia Ch
Abstract : Novel treatment strategies are needed for breast cancer chemoprevention. Tamoxifen is the only drug approved for the chemoprevention of estrogen receptor-positive breast cancer. However, to date, no treatment exists for the chemoprevention of estrogen receptor-negative breast cancer. NSAID use is associated with a reduced risk of breast cancer. However, the biological mechanisms underlying the effect of NSAID on breast cancer are not well defined. NSAIDs inhibit cyclooxygenases, thus preventing the formation of prostaglandins, prostacyclin, and thromboxane. NSAIDs also exert other biological effects, including generation of reactive oxygen species and inhibition of nuclear factor-κB-mediated signals. This review synthesizes the evidence on the COX-2-independent mechanisms of action of aspirin, salicylates, and other NSAIDs on breast cancer.